Recent Advances in Highly Fluorescent Hydrazine-Inserted Pyrrole-Based Diboron-Anchoring Fluorophores: Synthesis and Properties - Yu, Changjiang; Sun, Yingzhu; Jiao, Lijuan; Hao, Erhong (Synlett, 2023)
Hydrazine-inserted pyrrole-based diboron fluorophores that display strong fluorescence in either the solution or solid state are widely used in biomedicine and optoelectronic materials science. A growing demand calls for multiple strategies for generating novel fluorophores to solve problems of small Stokes shifts and poor solid-state fluorescence. By changing their frameworks, several series of novel diboron compounds have recently been developed as increasingly valuable classes of fluorophores owing to their tunable structures and outstanding spectroscopic properties, such as high fluorescence quantum yields, large Stokes shifts, high photostability, and low LUMO energy levels due to the presence of electron-deficient BF2 groups. This review mainly highlights key synthetic strategies for the fluorophores BOPHY, BOPPY, and BOAPY developed by our group, together with the superior properties of these compounds. Significant photophysical data for these fluorophores in solution and solid states are included within the scope of this review. The facile functionalization of these fluorophores permits practical structural modifications to generate novel versatile dyes with excellent chemical and photophysical properties. We believe that these fluorophores hold promise to make important contributions in a wide range of applications.1 Introduction2 BOPHY Fluorophore2.1 Discovery of BOPHY and its Fundamental Properties2.2 Synthesis and Properties of Modified BOPHY Derivatives3 BOPPY and BOPYPY Fluorophores3.1 Discovery of BOPPY and BOPYPY, and Their Fundamental Properties3.2 Synthesis and Properties of Benzo-Fused BOPPYs from Isoindoles3.3 Nucleophilic Substitution and Cross-Coupling Reactions of Halogenated BOPPYs3.4 Knoevenagel Reaction4 BOAPY and BOPAHY Fluorophores5 Conclusion
Keywords: fluorescent dyes; boron-containing dyes; B,N-heterocycles; fluorophores